1995
DOI: 10.2165/00003495-199549010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual Syndrome

Abstract: Premenstrual syndrome is a legitimate illness consisting of the cyclic recurrence of symptoms (physical, mental and behavioural) in the late luteal phase of the menstrual cycle of sufficient severity to require treatment. The syndrome has a yet unknown aetiology, an uncertain and variable course, and an unidentified family history. Methods are available for diagnosis including obtaining a reliable history, thorough physical and mental examinations, laboratory tests to exclude other possible causes of symptoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Although the etiological basis underlying these sex differences is unknown, one should take into account hormone status. [20][21][22][23] Moreover, female predisposition to the asymptomatic form of MPS in the lower limbs has been confirmed. 24 Thus, one has to assume that nociplastic pain may result from the response to a prolonged LBLP or can develop due to mechanical posture overloading or muscle involvement during the acute phase of disc disease.…”
Section: Discussionmentioning
confidence: 89%
“…Although the etiological basis underlying these sex differences is unknown, one should take into account hormone status. [20][21][22][23] Moreover, female predisposition to the asymptomatic form of MPS in the lower limbs has been confirmed. 24 Thus, one has to assume that nociplastic pain may result from the response to a prolonged LBLP or can develop due to mechanical posture overloading or muscle involvement during the acute phase of disc disease.…”
Section: Discussionmentioning
confidence: 89%
“…This is consistent with the findings of Fricton et al [ 2 ] and Drewes and Jennum [ 10 ], both of which found that MPS is more prevalent in female than male patients. This was attributed to the hormonal changes in women, whereby pain was reported to increase during the second week of the menstrual cycle [ 11 ]. More extensive research into this matter is warranted in order to establish the possible causal relationship between female gender and MPS.…”
Section: Discussionmentioning
confidence: 99%
“…According to SK Severino et al, some hormonal changes attributing to MPS in females and pain was reported to increase during second week of menstrual period. [22] Anette Kaergaard et al [23] assessed the occurrence of two restrictively defined neck-shoulder disorders among sewing machine operators among 243 patients where job involves monotonous, highly repetitive tasks performed in a sitting working posture with upper back curve and head bent over the sewing machine. Es Rachlin [24] said, occupational or recreational activities that produce repetitive stress on a specific muscle or muscle group commonly cause chronic stress in muscle fibres, leading to trigger points due to improper body mechanics.…”
Section: Discussionmentioning
confidence: 99%